IMPLEMENTATION OF INNOVATION STRATEGY MANAGEMENT FOR DEVELOPING THE ELECTRIC VEHICLE ECOSYSTEM - Rio Afrianda (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the application of innovation strategy management in the development of the electric vehicle (EV) ecosystem in Indonesia, using a technical case study of Lithium Polymer (LiPo) battery testing at the PT PLN Nusantara Power Muara Karang public charging station (SPKLU). Experimental results demonstrated that a BLDC motor powered by a 54.6 V 40 Ah LiPo battery could operate efficiently, providing an energy capacity of approximately 2,184 Wh. The charging process from a State of Charge (SOC) of 33% to 99% required 5 hours and 20 minutes with a 5 A current, while the charging temperature ranged from 28.2 °C to 41.6 °C, remaining within the safe operating limits (–5 °C to 45 °C). Discharge testing under average load currents of 2.6 A and 3.7 A indicated operating times of approximately 8 hours and 7 hours, respectively, , effective Battery Management Systems (BMS), and safe thermal characteristics are critical enablers for EV adoption. Furthermore, accelerating the EV ecosystem in Indonesia requires strengthening battery research, advancing fast-charging infrastructure, implementing innovative business models, and ensuring multi-stakeholder synergy. with battery voltage decreasing proportionally with SOC reduction. These technical findings were further interpreted through the lens of innovation strategy management, encompassing technological innovation, business model adaptation, regulatory support, and cross-sector collaboration. The results highlight that reliable battery performance